Examination of an E-Blended Learning Training Experience Including Sports Facilities - Juan Luis Moreira (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. The aim of the study is to identify particular tactics that enhance the intrinsic motivation and engagement of students in online training activities. Materials and methods. This article presents the outcomes of a training programme that combined e-learning and blended learning on the Moodle platform. The programme involved 90 sports technicians and utilised a cooperative teaching approach, benchmarking, and the forum as the primary teaching resource. Results. The findings of the experiment demonstrate the significant influence that the instructor plays in the advancement of training initiatives, alongside the design of the platform and the resources provided. This demonstrates that the forum, enquiries, tasks, and databases receive more visitors compared to the presentations, videos, and complementing articles. Conclusions. In this experience, it is important to emphasize the significance of the Moodle platform and its resources as effective means of communication and learning for both students and instructors.